Cassia fistula: A remedy from Traditional Persian Medicine for treatment of cutaneous lesions of pemphigus vulgaris - Fatemh Atarzadeh; Amir Jaladat; Ladan Dastgheib; Gholamreza Amin; Majid Nimrouzi; Mohammad Kamalinejad (Mashhad University of Medical Sciences, 2017)
Objective: Pemphigus is a rare autoimmune disease that may be fatal without proper medical intervention. It is a blistering disease that involves both the skin and mucus membranes, in which the most important causes of death comprise superimposed opportunistic infections and complications of long-term high-dose corticosteroid therapy or prolonged consumption of immune suppressant drugs. Skin lesions are the most important sources of infection, and any local treatment decreasing the healing time of lesions and reducing the total dosage of drugs is favorable. Materials and Methods: Here, we review the probable mechanism of action of a traditional formulary of Cassia fistula (C. fistula) fruit extract in almond oil as a new topical medication for reducing the duration of treatment of pemphigus vulgaris erosions. Result: C. fistula fruit oil has lupeol, anthraquinone compounds as rhein and flavonoids. Previous in vitro and animal studies on C. fistula fruit have demonstrated wound healing, antioxidative, anti-leukotrienes, anti-inflammatory, antibacterial and antifungal effects of this plant. Conclusion: It is hypothesized that C. fistula L. can be a botanical therapeutic choice for treatment of pemphigus erosions.